On the Effects of the Frequency Frame on DC Motor Example: Fractional Order PI-PD Case - Demiroglu, Ugur; Senol, Bilal; Matusu, Radek (Ieee, 2019)
This is a comparative study investigating the effects of the controller design method, frequency frame on a DC motor example. Both fractional order proportional integral and proportional derivative controllers are designed for mentioned example which is a first order plus time delay model. The two controllers are in different structures in that they can show different behaviors. The frequency frame approach is a frequency domain method which intends to provide the objective system improved stability and robustness by shaping the Bode curves. In contrary to existing similar methods, shaping is done by a graphical point of view, not by complicated mathematical operations. The reason why a fractional order controller is selected comes from the necessity of a common constant. The study in the paper aims to show the effectiveness of the frequency frame by providing desired frequency specifications with different controllers. Both controllers are calculated for a DC motor transfer function and the comparative results are given.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 21-22, 2019 -- Inonu Univ, Malatya, TURKEY
Keywords: Frequency frame; fractional order; proportional integral; proportional derivative; loop-shaping; DC motor